Creativity in the Advertisement Domain: The Role of Experience on Creative Achievement - Agnoli, Sergio; Mastria, Serena; Kirsch, Christiane; Corazza, Giovanni Emanuele (Frontiers in Psychology, 2019)
The creativity of an advertisement campaign is one of the most relevant predictors of its success. Past research has highlighted the relevance of domain-specific experience in enhancing creativity, but the results are controversial. We explored the role of work experience, in terms of number of years spent in the advertisement domain, on various forms of creativity expressed within this specific working domain. We hypothesized a mediator role of experience in the relationship between the individual’s creative potential, as measured through a series of divergent thinking tasks, and creative achievement in the advertisement domain. Moreover, considering the importance of personality on creative achievement, we also explored the influence of the openness-to-experience on advertisers’ creative achievement. A range of measures assessing creative achievement, openness, and divergent thinking abilities in terms of fluency and originality were administered to a group of professionals in the advertisement domain. The results demonstrate a crucial role for experience in the connection between originality and creative achievement. Moreover, our findings extend previous studies by showing that fluency and openness are significant predictors of creative achievement in the advertisement environment. These results emphasize the importance of canalizing the advertiser’s divergent thinking abilities through appropriate routes provided by working experience, raising important implications for future explorations of domain-specific creative achievement within an individual differences framework. Final indications for future developments are provided, with a special emphasis on the replication of these findings in various work domains and in various cultural contexts.